The Effect Of The Problem-Based Learning Model Through A Differentiated Approach To Motion Material On The Learning Outcomes Of Students In Grade VII Of MTS Nurul Bahri Kabila Bone - Samawati, Alfandi; Abdjul, Tirtawaty; Ntobuo, Nova Elysia (International Journal of Technology and Education Research, 2025)
This study was conducted to determine the effect of applying the Problem-Based Learning (PBL) model through a differentiated approach on students' learning outcomes in the subject of Motion. The type of research used was an experiment with a One Group Pretest-Posttest Design. The research population included all seventh-grade students at MTs Nurul Bahri Kabila Bone, while the research sample consisted of three classes, namely the experimental class, replication 1, and replication 2, which were determined using the Cluster Random Sampling technique. The research instruments included learning style tests, teaching modules, Student Worksheets (LKPD), teaching materials, and written tests in the form of pre[1]tests and post-tests used to measure student learning outcomes. The data obtained were analyzed using descriptive and inferential statistics, including normality tests, hypothesis tests, and N-gain analysis. The results showed that the average learning outcome score of students in the experimental class was 83.92, in replication class 1 was 83.67, and in replication class 2 was 82.92. Based on the normality test results, the data was declared to be normally distributed. The N-gain analysis showed that the increase in learning outcomes was in the high and moderate categories. The hypothesis test showed that the t-count values for each class, namely 26.422 for the experimental class, 10.52 for replication class 1, and 18.877 for replication class 2, were greater than the t-table. Thus, it can be concluded that the application of the Problem-Based Learning (PBL) model through a differentiated approach has a significant effect on student learning outcomes.